Synthesis and Characterization of Magnetite Nanocomposites for Photocatalytic Reactions - Kaur, Kamaljeet (My University, 2017)
The heterogeneous catalysis for photodegradation of cationic and anionic dyes was carried out by mesoporous magnetite nanoparticles (m-Fe3O4) and series of M containing magnetite nanoparticles where (M = CeO2, TiO2, SiO2 and Au nanoparticles). m-Fe3O4 nanoparticles were synthesized by modified co-precipitation method with BET surface area 60.2 m2g-1. The M substituted nanocomposites were synthesized by hydrothermal method. The octahedral occupancy of M increased the BET surface area. Highest surface area was achieved with SiO2/Fe3O4 was (120.5 m2g-1). Samples were characterized by XRD, FTIR, SEM, VSM and BET surface area. Methyl orange and methylene blue were chosen as model anionic and cationic dyes respectively for photodegradation studies. Photodegradation of methyl orange (90.4%) with CeO2/Fe3O4 and methylene blue (91.4%) with SiO2/Fe3O4 was achieved and it found to be efficient by using M/Fe3O4 NPs compared to the Fe3O4 alone. The M incorporation has significantly improves the catalytic activity of the magnetite nanoparticles. These new experiences are of high significance for the natural use of M substituted magnetite nanoparticles for the purification of industrial wastewater
Keywords: Nanocomposite; magnetite; Photocatalyst